Development and Justification of Therapeutic Approaches for Abnormal Uterine Bleeding in Puberty - Diyora Pulatova (KLINIK VA FUNDAMENTAL TIBBIYOT TADQIQOTLARI JURNALI, 2026)
Abnormal uterine bleeding during the pubertal transition represents a profound pediatric and adolescent gynecological emergency, frequently precipitating severe hemodynamic instability, profound iron deficiency anemia, and extensive psychobehavioral distress. This prospective cohort investigation evaluates and standardizes etiology-driven therapeutic interventions for adolescent females experiencing acute and chronic heavy menstrual bleeding. Analyzing a strictly phenotyped cohort of 312 patients aged 11 to 17 years admitted between 2020 and 2024, the study quantifies the clinical efficacy of tiered pharmacological strategies, including targeted antifibrinolytic therapy, non-steroidal anti-inflammatory drugs, and specific hormonal regimens. Clinical parameters, encompassing Pictorial Blood Loss Assessment Chart scores, hemoglobin kinetics, coagulation cascades, and pelvic ultrasonography morphometrics, were synthesized using multivariate logistic regression frameworks. The etiological breakdown identified anovulatory dysfunction secondary to hypothalamic-pituitary-ovarian axis immaturity as the predominant driver (65.4%), while underlying systemic coagulopathies accounted for a highly significant secondary subset (19.2%). The therapeutic analysis demonstrated that initial intervention utilizing intravenous tranexamic acid combined with high-dose oral progestins arrested acute hemorrhagic episodes within 36 hours in 84.6% of patients, circumventing the need for surgical hemostasis entirely. Long-term stabilization using combined oral contraceptives yielded a 91.2% success rate in preventing recurrent hospital admissions over a 12-month follow-up period, outperforming sequential progestin therapies. These findings mandate an immediate departure from generalized adult gynecological protocols. Recognizing the unique neuroendocrine and hematological vulnerabilities of the adolescent patient requires the deployment of age-specific, etiology-based algorithms, directly optimizing acute hemostatic recovery and safeguarding long-term reproductive potential.